Observing the mass-loss of nearby red supergiants through high-contrast imaging. Issue Volume 14:Issue S343(2019) (August 2018) - Scicluna, Peter; Siebenmorgen, R.; Blommaert, J. A. D. L.; Kemper, F.; Wesson, R.; Wolf, S.
Abstract: We present observations of nearby red supergiants with SPHERE.